Clinics and Peculiarities of the Course of Combined Viral Hepatitis - Axmedova Dildarxon Kabilovna (Genius Journals, 2023)
Conducted clinical and serologic examination of 1400 children aged 0-14 with acute viral hepatitis in order to reveal the etiology of hepatitis and the number of combined forms among them was performed. During our investigation we revealed some peculiarities in clinical course, clinical symptoms and aggravation of the disease in case of combined course of VHB and VHC. In case of combination of AVHA+AVHB and AVHA associated with HBSAg significant prolongation of remission was noted. Among 294 patients with A VHB acute delta-viral infection was revealed in 51 persons. It gave the possibility to determine some clinical peculiarities and differentiations of VHD in case of co - infection and super infection. The obtained data allows to prognosticate frequency of different forms of VH in the region and help to perform rational measures on decreasing YH morbidity.
Keywords: combined hepatitis; morbidity; clinical peculiarities